Monetary policy and economic development in Nigeria : a festschrift in honour of Professor Siyanbola Tomori - Fakiyesi, Oluwatayo; Adebiyi, Michael Adebayo; Department of Economics, University of Lagos (Lagos, Nigeria : University of Lagos Press, 2012)
A compilation of articles on issues relating to monetary policy and economic development in Nigeria. It evaluates the critical monetary policy issues such as the flow of credit, the payment system and other economic development matters relevant to a developing economy such as Nigeria.
Includes bibliographic references.
oif 18/09/14
Loan
Keywords: Monetary policy; Economic development; Nigeria